2021
DOI: 10.1080/21655979.2021.1906028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-level ultrasound treatment on the production of L-leucine by Corynebacterium glutamicum in fed-batch culture

Abstract: Various process intensification methods were proposed to improve the yield, quality, and safety of fermented products. Here, we report the enhancement of L-leucine production by Corynebacterium glutamicum CP using ultrasound-assisted fed-batch fermentation. Response surface methodology was employed to optimize the sonication conditions. At an ultrasonic power density of 94 W/L, frequency of 25 kHz, interval of 31 min, and duration of 37 s, C. glutamicum CP produced 52.89 g/L of L-leucine in 44 h, representing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Under low power sonication, the activity of crude enzyme solution increased with increasing sonication power; the highest activity of 107 U/mL was achieved under the treatment condition of 150 W. However, with further increases in power, the activity showed a trend of weakening. Analysis showed that low-power ultrasound could induce stable cavitation in the surrounding liquid, and the generation and extinction of cavitation bubbles can cause oscillations in the liquid ( Rao and Rathod, 2014 ; Gonçalves et al, 2015 ), which in turn causes changes in the structure of the cell membrane, increasing its permeability to some extent and even disrupting it, causing enzyme molecules to flow from inside the cell to outside the cell ( Zhang et al, 2021 ), and ultrasound produces benign changes in the structure of enzyme molecules ( Wang et al, 2012 ), leading to further increases in enzyme activity. As a result, enzyme activity tends to increase.…”
Section: Resultsmentioning
confidence: 99%
“…Under low power sonication, the activity of crude enzyme solution increased with increasing sonication power; the highest activity of 107 U/mL was achieved under the treatment condition of 150 W. However, with further increases in power, the activity showed a trend of weakening. Analysis showed that low-power ultrasound could induce stable cavitation in the surrounding liquid, and the generation and extinction of cavitation bubbles can cause oscillations in the liquid ( Rao and Rathod, 2014 ; Gonçalves et al, 2015 ), which in turn causes changes in the structure of the cell membrane, increasing its permeability to some extent and even disrupting it, causing enzyme molecules to flow from inside the cell to outside the cell ( Zhang et al, 2021 ), and ultrasound produces benign changes in the structure of enzyme molecules ( Wang et al, 2012 ), leading to further increases in enzyme activity. As a result, enzyme activity tends to increase.…”
Section: Resultsmentioning
confidence: 99%
“…The metabolic functions of l -leucine in regulating muscle protein synthesis and insulin release have high commercial value in the feed industry [ 3 , 4 ]. Therefore, the increasing market demand for this amino acid has stimulated interest in the development of cost-effective approach for its production on an industrial scale [ 5 ]. Currently, mutagenesis and metabolic engineering strategies are the common methods used to engineer cellular factories for l -leucine production [ 6 ].…”
Section: Introductionmentioning
confidence: 99%